’Varietal screening of grasspea (Lathyrus sativus) in presence or absence of Rhizobium inoculation - BHUIYAN, M A; KHANAM, D; KHATUN, M R (The Indian Journal of Agricultural Sciences, 2013)
Grasspea. (Lathyrus sativus L.) varieties ’8603’, ’8604’ and ’Jamalpur Local’ were inoculated with Rhizobium strain RLs 10. Seed inoculation with this bacteria enhance,d nodulation, dry-matter weight and yield of grasspea cultivars under field conditions. Results of 3-year observation showed that the advance lines ’8603’ and ’8604’ which had maximum nodulation did not give a high seed yield and ’Jamalpur Local’ recorded maximum seed yield but did not show high nodulation as in the advance lines ’8603’ and ’8604’. The advance line ’8603’ produced highest nodule number (62.7,52.2 and 39.l/plant), nodule weight (81, 57 and 69 mg/plant) but ’Jamalpur Local’ recorded highest seed yield (1.67, 1.48 and 1.73 tonnes/ha) owing to inoculation in 1991-92, 1992-93 and 1993-94 respectively.